1998
DOI: 10.1111/j.1365-2672.1998.tb05277.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and structure of drinking water biofilms and techniques for their study

Abstract: Drinking water systems are known to harbour biofilms, even though these environments are oligotrophic and often contain a disinfectant. Control of these biofilms is important for aesthetic and regulatory reasons. Study of full-scale systems has pointed to several factors controlling biofilm growth, but cause-and-effect relationships can only be established in controlled reactors. Using laboratory and pilot distribution systems, along with a variety of bacterial detection techniques, insights have been gained o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 54 publications
0
44
0
Order By: Relevance
“…Poultry drinking water systems allow sediment accumulation on pipe walls and tanks (Fig. 1), partly explaining the wide diversity of eukaryotes that was detected in the water systems (11,53). The central role of protozoa in aquatic food webs as major grazers of phytoplankton and bacteria is firmly Campylobacter and protozoan epidemiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poultry drinking water systems allow sediment accumulation on pipe walls and tanks (Fig. 1), partly explaining the wide diversity of eukaryotes that was detected in the water systems (11,53). The central role of protozoa in aquatic food webs as major grazers of phytoplankton and bacteria is firmly Campylobacter and protozoan epidemiology.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the presence of disinfectant, low temperatures, and flow regimes in drinking water distribution systems, the growth and persistence of bacteria in is well documented, and the diversity of protozoa and number of organisms are usually a function of the amount of available organic matter, including bacterial load (11,53). Poultry drinking water systems allow sediment accumulation on pipe walls and tanks (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Among these are the recovery of total coliforms from distribution systems in which water leaving the treatment plant tested negative for coliforms (20,21); the observation that environmentally derived strains of total coliforms and E. coli can grow in unsupplemented distribution system water (7); and the recovery of increased numbers of E. coli organisms from drinking water distribution pilot plants after the calculated inoculum should have theoretically washed out (12). Other studies have shown that E. coli can attach and become incorporated into biofilms within model distribution systems (8,11), as well as into biofilms derived from groundwater populations (2). In recent years, the advent of molecular detection techniques has greatly facilitated our understanding of bacteria indigenous to the environment.…”
mentioning
confidence: 99%
“…In the kitchen, a variety of normal domestic wastes will pass through the drain conduit, especially where waste disposal units are fitted, along with residues from high-risk infectious materials, such as uncooked meat (12) and vegetable waste (15). Additionally, potential pathogens, including pseudomonads and Legionella pneumophila, may also enter the drain through tap water (6,20,27). Domestic sink drain biofilms therefore represent a largely unstudied nidus for potentially pathogenic bacteria, situated close to food preparation areas.…”
mentioning
confidence: 99%